Taenia saginata taeniosis: copro-antigen time-course in a voluntary self-infection. Issue 5 (September 2015) - Tembo, A.; Craig, P.S.
Abstract Human taeniosis due to Taenia saginata is cosmopolitan where beef is consumed; however, there is little or no information on the symptomatology over the early time-course of human infection. Copro-antigen detection is very useful in community screening for human taeniosis, particularly for T. solium, but there are no data on copro-antigen detection in pre-patent infection. In order to provide insight into this, a voluntary self-infection with T. saginata was undertaken and monitored over a 6-month period using a copro-antigen enzyme-linked immunosorbent assay (ELISA) that we developed using anti-T. saginata antibody based reagents. Tapeworm patency, defined as first proglottid appearance, occurred on day 86 post-infection (pi) and was followed by almost daily release of proglottids (range 1–8) until termination using praziquantel on day 180 pi. The first 10 weeks post-infection (wpi) were essentially asymptomatic, followed by main symptoms of involuntary proglottid discharge throughout the infection period, and abdominal discomfort peaking around 15–19 wpi. Copro-antigens could not be reliably detected until 2 weeks before proglottid patency but then remained highly elevated over the next 15 weeks until treatment. Copro-antigen levels reverted to negative 4 days post-treatment. This time-course study suggests that although copro-antigen ELISA is an excellent diagnostic tool for established patent infections of T. saginata, it may not be reliable for faecal antigen detection in the early infection phase prior to proglottid release for T. saginata and other human taenioses.